Calculation parameters of Kapshagay water reservoir in multiyear regulation for sustainable development of Lake Balkash (Journal of Geography and Environmental Management, 2017)
This article presents the methodology, scientific and technical bases, and results of research on the Kapshagai reservoir adjustment parameters in the following order:– calculation of losses water on the delta of Ile River and in the inflow of the Lake Balkhash;- recommended water management measures adopted in accordance with the «Sustainable development scenarios by the Russian State Institute of Hydrology» (SDS RSIH);- Hydrological and water calculations to identify the Kapshagai reservoir parameters.The adopted methodology and the scientific-technical basis for the study of social, environmental and economic performance measures to adjust the operating parameters of reservoirs in the multiyear regulation. Adjusted parameters of the Kapshagai reservoir in an average water flow year in line with the proposed methodology, and scientific and technical basis for the water supply of water complex P= 95%, the mark of the dead volume EMA = 474 m (12.8 km3) and normal water level NWL = 480 m (19.8 km3).